Peningkatan Kemampuan Motorik Halus Melalui Kegiatan Mozaik Pada Siswa Kelompok B - Qomariah, Qomariah; Marlina, Leny; Oktamarina, Lidia (Journal of Early Childhood Education (JECE), 2020)
The undeveloped child's fine motor ability is the background for this research. The problems in this study were child's undevelopment ability to control fingers and hands, undevelopment of skills using media with the coordination between eyes and hands. The subject of his research was the B3 group of 18 children. This was based on action research method. It used the Kemmis & McTaggart Research design which consists of planning, observation and reflection actions. There were two cycles with four times meeting in each cycle. Data used in the observation were field records, interview notes and documentation notes. The techniques of data analysis in this study were qualitative data analysis and quantitative data analysis. The results showed that in the pre-cycle phase, the child's fine motor ability level reached 47.66%, whereas after using mozaic activities in cycle 1 it reached until 59.91% and in cycle 2 it reached to 80.08%. It can be concluded that there is a significant increase in the child's fine motor ability through mosaic activities.